2022
DOI: 10.1186/s13031-022-00455-z
|View full text |Cite
|
Sign up to set email alerts
|

The boundaries between complex posttraumatic stress disorder symptom clusters and post-migration living difficulties in traumatised Afghan refugees: a network analysis

Abstract: Background Psychological distress due to the ongoing war, violence, and persecution is particularly common among Afghan asylum seekers and refugees. In addition, individuals face a variety of post-migration living difficulties (PMLDs). Complex posttraumatic stress symptoms are among the most common mental health problems in this population, and were associated with the overall burden of PMLDs. The complex interplay of posttraumatic symptoms has been investigated from a network perspective in pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(10 citation statements)
references
References 67 publications
0
10
0
Order By: Relevance
“…98 Poor mental health lingers for long periods after resettlement, 99 given that the associations between trauma exposure and clinical symptoms are moderated through the presence of ongoing stressors and loss of coping resources. 100 Post-resettlement stressors include a state of precarity with regards to residence status, 101,102 loneliness, 93,103 acculturation difficulties, 104 unemployment, intergenerational conflicts, 59 gender role changes, 105,106 discrimination, 107 education and inclusion. 108,109…”
Section: Resultsmentioning
confidence: 99%
“…98 Poor mental health lingers for long periods after resettlement, 99 given that the associations between trauma exposure and clinical symptoms are moderated through the presence of ongoing stressors and loss of coping resources. 100 Post-resettlement stressors include a state of precarity with regards to residence status, 101,102 loneliness, 93,103 acculturation difficulties, 104 unemployment, intergenerational conflicts, 59 gender role changes, 105,106 discrimination, 107 education and inclusion. 108,109…”
Section: Resultsmentioning
confidence: 99%
“…For example, experiences of discrimination have been found to have a strong association with negative self-concept, while residency instability has been associated with re-experiencing symptoms. 11 These results highlight the complex dynamics between history of trauma, the presence of ongoing stressors and trauma-related mental health symptoms.…”
Section: Prevalence Risk Factors and Symptom Profilementioning
confidence: 88%
“…Insecure visa status predicted PTSDICD-11 and cPTSD class membership in a study with refugees in Australia (71), and in Afghan refugees in Austria the cPTSD cluster was associated with more problems with language acquisition and barriers (72). There were no associations between PTSDICD-11 or cPTSD and employment (60,62,64,66), family concerns (65,72), residence insecurity, socioeconomic living conditions and discrimination (72), legal status (64), and being with family (60).…”
Section: Factors Associated With Ptsd and Cptsdmentioning
confidence: 98%
“…Thirteen studies reported PTSDICD-11 prevalence rates (Figure 3), which ranged from 0.4% (59) to 80% (48). Prevalence rates were higher in clinical samples (14.4% to 80%) (48,(60)(61)(62)(63)(64)(65)(66)(67) than in representative samples (0.4% to 20.9%) (43,58,59). The pooled prevalence of PTSDICD-11 was 21.3%.…”
Section: Prevalencementioning
confidence: 99%